Marine Environmental Plastic Pollution: Mitigation by Microorganism Degradation and Recycling Valorization - Oliveira, Juliana (2021)
UID/Multi/04378/2020 UID/CTM/50025/2020 Slovenian Research Agency (research core funding P1-0245)